Benefit Analysis of Long-Duration Energy Storage in Power Systems with High Renewable Energy Shares - Zhang, Jiazi; Guerra, Omar J.; Eichman, Joshua; Pellow, Matthew A. (Frontiers in Energy Research, 2020)
The integration of high shares of variable renewable energies raises challenges for the reliability and cost-effectiveness of power systems. The value of long-duration energy storage, which helps address variability in renewable energy supply across days and seasons, is poised to grow significantly as power systems rely more exclusively on variable generation such as wind and solar. In this study, the system-level services and associated benefits of long-duration energy storage on the 2050 Western Interconnection (WI) are explored. The operations of the future WI system with 85% renewable penetration is simulated using a two-stage production cost model. Four long-duration technologies with different round-trip efficiencies are studied for the 2050 WI system. The energy storage performance, system production cost reduction benefits from diurnal and seasonal operation, and impacts on generation mixture, and curtailed renewable energy are fully assessed.